Inhibiting Factors for Publishing in Reputable International Journals among Doctoral Students : An Exploratory Mixed Method Study - PURWANTO, AGUS; Ardiyanto, Jeffri; Sudargini, Yuli (Journal of Industrial Engineering & Management Research, 2021)
This study aims to explore the inhibiting factors of Indonesian doctoral students in carrying out reputable international publications. This research is a sequential mixed method exploration with qualitative exploration methods and to determine the relationship between the inhibiting factors of publication performance and quantitative methods. This study used a mixed sequential exploratory method. The first step was a qualitative analysis that explored the inhibiting factors for doctoral student publication. Primary data collection used open and unstructured interviews in depth to 7 (seven) doctoral program student participants who were selected and determined using purposive sampling method. The second step is to conduct a quantitative analysis to determine the correlation between inhibiting factors and publication performance. Primary data collection used an online questionnaire with 250 respondents selected using the snowball sampling method and then analyzed using the SmartPLS program. The results of this study indicate that the doctoral program student respondents have several obstacles to publishing in internationally reputable journals such as negative results, lack of funding, long response time, low English language skills, insufficient writing time, limited writing skills, limitations. submission capability. , high publication costs, inadequate facilities, limited journal references, limited technology skills. The novelty of this research is the first research on obstacles in the publication of doctoral students in Indonesia using the Exploratory Sequential Mixed Methods with the scope of a country. This research can serve as a reference for similar research, and further research can be carried out in other countries.